Validation of a teacher mathematics knowledge scale based on the Ernest framework among Malaysian teachers - Nor Hasnida binti Che Md Ghazali, Syaza Hazwani binti Zaini, Mahizer bin Hamzah, Noor Insyiraah binti Abu Bakar (Tanjung Malim, 2024)
Validation of a teacher mathematics knowledge scale based on the Ernest framework among Malaysian teachers by Nor Hasnida binti Che Md Ghazali, Syaza Hazwani binti Zaini, Mahizer bin Hamzah, Noor Insyiraah binti Abu Bakar